HUBUNGAN ASUPAN ENERGI, PROTEIN HEWANI DAN PROTEIN NABATI DENGAN MASSA OTOT PASIEN CA. MAMAE DI RSUD DR H ABDUL MOLOEK: The Correlation of Energy Intake, Animal Protein and Plant Protein With Muscle Mass in Breast Cancer Patients at Dr. H Abdul Moloek Hospital - Yustini, Fatmawati; Khairani, Masayu Dian; Junita, Dera Elva; Wati, Desti Ambar (Media Gizi Pangan, 2024)
A leading cause of death in Indonesia, with a fatality rate as high as 17.0%, is breast cancer. Energy consumption affects how proteins are metabolized during the growth of muscle mass, and eating both plant- and animal-based proteins is important for maintaining and increasing muscle mass. The purpose of this study was to look into the relationship between the amount of muscle mass and the calorie intake and consumption of animal and vegetable proteins among breast cancer patients. Using the quota sampling technique, 56 out of 291 patients with stage 2 breast cancer, ages 22 to 26, were selected for the study sample The research design was cross-sectional. Muscle mass was measured with a Karada Scan, and data on energy intake, animal protein, and vegetable protein were collected using a 3x24-hour recall. Analysis was done using the Spearman Rank test. The average calorie intake was determined to be 888.28 kcal, with 18.43 g of animal protein and 21.10 g of vegetable protein. Animal and vegetable protein did correlate (p-value = 0.000 and 0.001, respectively) with muscle mass, however energy and muscle mass did not (p-value = 0.664).